Burkina Faso : 2016 Article IV Consultation, Sixth Review Under the Extended Credit Facility, and Request for Modification of a Performance Criterion, Extension of the Arrangement and Augmentation of Access-Press Release; Staff Report; and Statement by the Executive Director for Burkina Faso. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights a rebound in economic activity in Burkina Faso beginning in 2016, after two years of weak growth. The January terrorist attacks and delays in approving the budget weighed on activity in the early part of 2016, but activity has rebounded, and real GDP growth is now projected at 5.4 percent, an improvement over 4.0 percent in 2015. The recovery is led by two new gold mines that came onstream and a sharp projected rebound in agricultural output in late 2016 and early 2017, after three disappointing years. The recovery is expected to consolidate in 2017, and growth is projected to rise to 6.1 percent as domestic and external conditions remain supportive.